The Application of Tetragon Analysis in A Sample of Kurdish Adult Population with Class I Occlusion:A Cephalometric Study - Ziyad Jamil Al-Talabani , Shaho (Diyala Journal of Medicine, 2021)
Background: Visual cephalometric analysis is a simple, logical, and accurate diagnostic tool for the student, the clinician, and the researcher. The analysis is elicited from two geometric constructs, the Tetragon and the Trigon. Objective: To determine the cephalometric norms as per Fastlicht’s analysis for male and female subjects of the Kurdish population and to compare these cephalometric norms with Fastlicht’s norms, average Caucasian norms, and Iraqi (non-Kurdish) norms. Patients and Methods: The cephalometric radiographs of 63 individuals, 25males, mean age 23.01 ±2.9 years, and 38 females, mean age 23 ± 3.2 years, were selected. FACAD 3.4.0.3, an orthodontic tracing software for cephalometric analysis and treatment planning, was used to digitally trace the reference points and reference lines for the tetragon analysis. Results: The statistical differences between the data of the Iraqi Kurdish population and the data of Fastlich, average Caucasian, and Iraqi non-Kurdish population were significant. Conclusion: The data of the Kurdish population is different from that of Fastlich and non-Kurdish Iraqi data. It is recommended to use this study's findings to get a more accurate result for the Iraqi Kurdish population when using tetragon analysis.